Accurate Software Implementation For Accounting Information System Corporate (Case Study Yanata) - Ong Felycia Christiana; Rinabi Tanamal; Kartika Gianina Tileng (Forum Manajemen Indonesia (FMI), 2015)
Financial bookkeeping is the most important thing in any company. Bookkeeping manually using books and calculator, often make a lot of mistakes in calculations and accuracy. Digital bookkeeping make easier for companies to store data and evidence for each record that will be used in the books of each company.